2014
DOI: 10.1097/dcc.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Receipt of Physical Therapy Consultation in Patients Requiring Prolonged Mechanical Ventilation

Abstract: Background/Introduction Mobilization of critically ill patients in the intensive care unit (ICU) is associated with improved function at hospital discharge and reduced duration of mechanical ventilation (MV). Few studies, however, focus on physical therapy (PT) in patients on prolonged mechanical ventilation (PMV) despite their high risk of immobility and poor outcomes. Objective/Aims To identify factors associated with the receipt of PT consultation among patients requiring PMV. We hypothesized that key fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…2225 Early mobilization is limited by use of deep sedation and development of delirium, which can be minimized through the use of scale-based targeted light sedation is implemented early on. 26 …”
Section: Minimizing Sedationmentioning
confidence: 99%
“…2225 Early mobilization is limited by use of deep sedation and development of delirium, which can be minimized through the use of scale-based targeted light sedation is implemented early on. 26 …”
Section: Minimizing Sedationmentioning
confidence: 99%
“…Physical and functional deficiencies are common sequelae in patients admitted to ICUs 6 due to bed rest, which favors reduction of muscle mass and decrease of muscle efficiency and force 7 . These musculoskeletal changes also involve the vascular system (with decrease of venous return) and the respiratory system (due to respiratory muscle weakness), thus hindering the withdrawal of the MV 3,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Jolley et al 7 analyzed factors that influenced the performance of physiotherapy in patients on prolonged MV, and found that the septic shock did not interfere in the evolution of physiotherapy. We believe that the same has occurred in our study because, despite clinical patients having presented greater incidence of sepsis, this condition did not change the physiotherapeutic conduct with patients sitting as early than the surgical ones.…”
Section: Discussionmentioning
confidence: 99%
“…No more than half of patients in weaning centers receive adequate physical therapy with regard to its frequency and intensity [2022]. Nevertheless, it was confirmed that appropriate rehabilitation during hospital stay increases the BI approximately twofold and the weaning success by about 50% [21], while early mobilization is a positive independent factor contributing to being discharged home [23].…”
Section: Discussionmentioning
confidence: 99%